ONION SAPLING PLANTATION MACHINE - N. B. Jadhav1, S.P.Gavali 2, S.V.Chougule 2, U. T. Chavan 2, A.S.Madane 2 (International Journal of Innovations in Engineering Research and Technology, 2022)
The basic needs for small scale cropping machines are, they should be suitable for small farming fields, easy I design and technology and versatile for use in various farm operations. A manually operated template row planter was designed and implemented to improve planting efficiency and decrease drudgery involved in manual planting method. Seed planting is also possible for various size of seed at variable depth and space between two seed. Also, it increases seed planting, seed/fertilizer placement accuracies and it is made of durable and cheap material affordable for the small-scale peasant farmers. The usability, adjusting and maintaining principles are made simple for effective handling by unskilled operators (farmers).The hard work of farmers and time required to sow the seed and sapling is very time consuming. So, keeping in mind about the small-scale farmers we have made our project efficient, time saving and also affordable to the farmers.It becomes helpful to the farmers to transplant the saplings in good and efficient way. Onion growing farmers are experiencing challenges in planting onion seedlings because of a shortage of farming labour during the planting of onion crops. The objective of the project is to design an automated onion planting machine. Thus, a need for an automated onion planting machine developed. This device plants onion plants at predetermined intervals between each plant automatically, without any human intervention. Developing an onion planting machine that automatically plants onions in a row, reducing farmers' labour costs and time, was a major factor in its development.